Internal Financial Reporting Mechanism Realizing Bumdes Financial Accountability In Tompobulu District, Maros Regency - Syamsu Alam; Ratna Sari; Asriani Junaid; T. Tenriwaru; Ummu Kalsum; Eka Ariaty Arfah (Golden Ratio of Community Services and Dedication, 2021)
The goal to be achieved by this service activity is to increase the technical and conceptual knowledge capacity of Village-Owned Enterprises (BUMDes) managers regarding the preparation of financial reports and the BUMDes accountability process so that they can carry out financial control of BUMDes and can analyze company financial reports so that the performance of BUMDes can be improved. They were appropriately evaluated on an ongoing basis. The approach method used in this service activity is the method of counseling, training, and mentoring for four months, starting from June - December 2021, with the hope that partners can apply their knowledge about financial reporting mechanisms and how to measure BUMDes performance accountability. The result of implementing this service activity is that BUMDes managers gain knowledge and understanding of accounting policies and the process of preparing BUMDes financial reports. The manager will monitor and evaluate the business performance of BUMDes so that the business can be controlled at any time. BUMDes managers gain knowledge on how to analyze the financial condition of BUMDes in terms of liquidity ratios, solvency ratios, and profitability ratios. BUMDes managers will be able to manage their short-term assets and debt and analyze the profitability ratios (ROI and ROE). BUMDes managers gain insight into business development and how to generate profits from the assets used and BUMDes own capital.